Live S. aureus and heat-killed S. aureus induce different inflammation-associated factors in bovine endometrial tissue in vitro. (November 2021) - Liu, Kun; Mao, Wei; Liu, Bo; Li, Tingting; Wu, Jindi; Fu, Changqi; Shen, Yuan; Pei, Le; Cao, Jinshan
Highlights: HK-SA-treated group showed significantly higher IL-6, IL-1β, and TLR2 expression. LSA-infected group showed significantly higher PTGS2, mPGES-1, and EP4 expression. LSA induced PGE2 accumulation via the TLR2/MAPKs signaling pathway. Abstract: Staphylococcus aureus is majorly involved in bovine mastitis; however, it weakly induces pro-inflammatory factors in mammary gland epithelial cells. We aimed to clarify the involvement of S. aureus in other inflammation types and its relationship with inflammatory factor secretion in bovine endometritis. We used live S. aureus (LSA)- and heat-killed S. aureus (HK-SA)-treated bovine endometrial tissue in vitro . The HK-SA-treated group showed significantly higher IL-6, IL-1β, TNF-α, CXCL1/2 and TLR2 expression than the LSA-infected group. Contrastingly, the LSA-infected group showed significantly higher PTGS2, mPGES-1, and EP4 expression than the HK-SA treated group. There was no significant between-group difference in hyaluronan-binding protein 1 expression, which suggested similar inflammatory responses. H&E results indicated that LSA and HK-SA induced shedding of endometrial gland epithelial cells. The LSA-infected group showed higher high-mobility group box 1 protein expression than the HK-SA treated groups, which indicated differences in signaling pathway activation. Further, the LSA-treated group had higher JNK and p38 MAPK levels while the HK-SA-treated group had higher IκB-α levels. There was no significant between-group difference in the ERK signaling pathway. Our findings indicate that the pathogen-associated molecular patterns (PAMPs) of S. aureus activate pro-inflammatory factor expression via the TLR2-ERK-NF-κB signaling pathway. Contrastingly, LSA induced PGE2 accumulation via the TLR2/MAPKs signaling pathway. This is the first report that S. aureus and the PAMPs of S. aureus activate different signaling pathways and that LSA mainly induce PGE2 accumulation rather than cytokine secretion.